The problem of ICT policy translation: Contributions to overcome a technical rationality - Gary Alberto Cifuentes; María Camila Valbuena Osorio (Arizona State University, 2018)
Education policies for the use and appropriation of ICT (information and communication technologies) in Latin America are in their best moment. All across the region are emerging educational innovation systems aiming to close the gap of inequity and guarantee the access of quality education. Beyond a common discourse analysis approach on these national programs and their promises of development and productivity, it is necessary to understand what occurs locally when policy translations take place, that is, mobilization of actors, artifacts and heterogeneous practices. Drawing on policy enactment theory as a theoretical framework and using a comparative case study design, it is shown that beyond a technical rationality of ICT policy implementation or its interpretation by different actors, the problem of policy translation deserves a critical analysis from a sociomaterial approach. In order to underpin this work, a set of national programs for ICT integration are analyzed in Colombia, in three municipal contexts in which policy translation is performed through heterogeneous but effective forms enacting discourses on innovation and quality in education. This work is also a methodological contribution to map translations of educational policies, useful for researchers on this field.